Tips for developing a coaching program in medical education - Rebecca Miller-Kuhlmann; Marzena Sasnal; Carl A. Gold; Aussama K. Nassar; James R. Korndorffer; Sandrijn Van Schaik; Andrea Marmor; Sarah Williams; Rebecca Blankenburg; Caroline E. Rassbach (Medical Education Online)
This article provides structure to developing, implementing, and evaluating a successful coaching program that effectively meets the needs of learners. We highlight the benefits of coaching in medical education and recognize that many educators desiring to build coaching programs seek resources to guide this process. We align 12 tips with Kern’s Six Steps for Curriculum Development and integrate theoretical frameworks from the literature to inform the process. Our tips include defining the reasons a coaching program is needed, learning from existing programs and prior literature, conducting a needs assessment of key stakeholders, identifying and obtaining resources, developing program goals, objectives, and approach, identifying coaching tools, recruiting and training coaches, orienting learners, and evaluating program outcomes for continuous program improvement. These tips can serve as a framework for initial program development as well as iterative program improvement.